Study of bearing capacity of vibratory pile applying acceleration record - Kelevišius, Kęstutis; Gabrielaitis, Linas; Amšiejus, Jonas; Norkus, Arnoldas; Sikora, Zbigniew (Journal of Civil Engineering and Management, 2014)
The article focuses on the method for evaluation of ultimate bearing capacity for a vibratory pile having acceleration data recorded during the tests. The simulation vibratory pile installation test was performed in the testing stand. Accelerations were recorded on the top of the simulation vibratory pile during the test. The static test was performed for the installed pile. After the review of rheological models of the base, the Smith rheological model was chosen for determination of bearing capacity of the vibratory pile as this model, the rigidity of the final element of the spring is modelled as the finite rigidity of the base. Between the base of the modelled pile and the soil, a finite interface element is used. The interface element transfers only compression but it does not transfer tension to the base rheological model. The general stiffness of spring’s finite element in the chosen rheological model is determined from experimental data of the static pile test. During the modelling, the damping coefficients and the ultimate displacements (responses) of the pile’s shaft and base, to which the friction element became active, were determined so that the modelled pile accelerations and displacement (response) would coincide as much as possible with measured accelerations and their calculated response. The modelled and measured accelerations and responses showed high similarity.